Answer to Question #214932 in Differential Equations for Vimal

Question #214932

ut =9uxx

u(0,t)=u(2π,t) 0, t > 0

u(x,0) = {x , 0 < x < π

{- 3x, π < x < 2π


1
Expert's answer
2021-07-11T17:11:13-0400

"Given -"


"u_{t}=9u_{xx}"


so we can write this equation as =


"=\\dfrac{\\partial u}{\\partial t}=9\\dfrac{\\partial^{2} u}{\\partial u^ {2}}.....................................1)"


"=" "Boundry \\ conditions"


"u(0,t)=u(2{\\pi},t)=0,t>0"


Since "u(0," "t)" and "u(2{\\pi},t)" is given , so we will apply fourier sine transfrom with


"=\\ Initial\\ condition"


"u(x,0)=\\ {x},\\ 0<x<{\\pi}"


"\\ -{3x}" ",{-\\pi}<x<2{\\pi}"


"=" "\\int \\dfrac{\\partial u}{\\partial t}sin\\dfrac{2{\\pi}x}{2{\\pi}}dx=\\int 9\\dfrac{\\partial^{2} u}{\\partial u^ {2}}sin\\dfrac{2{\\pi}x}{2{\\pi}}dx"


"=\\dfrac{d}{dt}\\int_{0}^{2{\\pi}}usinxdx=" "9\\int_{0}^{2{\\pi}}\\dfrac{\\partial^{2} u}{\\partial u^ {2}}sin{x}dx"


"=\\dfrac{d\\hat{u_s}(s,t)}{dt}=-9s[u(x,t)cossx|_{0}^{2{\\pi}}+9s\\int_{0}^{2{\\pi}}usinsxdx]"


"=" "\\dfrac{d\\hat{u_s}(s,t)}{dt}=9s[u(2{\\pi},t)coss2{\\pi}-u_{(0,t)}]-9s^{2}\\int_{0}^{2{\\pi}}u(x,t)sinsxdx"



"\\because" "u({2{\\pi},t})=0=u_{(0,t)}"



"=" "\\dfrac{d\\hat{u_s}(s,t)}{dt}=-9s^{2}\\hat{u_s}(s,t).............................................4)"



where "\\hat{u_s}(s,t)=\\int_{0}^{2\\pi}u(x,t)sinsxdx"


Now solving equation 4) we get ,



"\\hat{u_s}(s,t)=9Ce^{-s^{2}t}..........................................5) , where \\ C\\ is\\ an\\ arbitrary\\ constant"




Put t=0 in equation 5) , we get ,


"c=\\hat{u_s}(s,0)=\\int_{0}^{2{\\pi}}u(x,0)sinsxdx"


As interval "0 \\ to\\ 2{\\pi}\\" is given in interval , so we have to also break the above integeral , so the integeral can be break like this .



"=" "\\hat{u_s}(s,0)=\\int_{0}^{2{\\pi}}u(x,0)sinsxdx=\\int_{0}^{{\\pi}}xsinsxdx-3\\int_{\\pi}^{2{\\pi}}xsinsxdx"



"=\\dfrac{\\pi(-1)^{s+1}}{s}-3\\dfrac{[{\\pi}s(-1)^{s}-2{\\pi}s]}{s^{2}}...................6)"



From 5) and 6) , we have -


"\\hat{u_s}(s,t)=""[\\dfrac{\\pi(-1)^{s+1}}{s}-3\\dfrac{[{\\pi}s(-1)^{s}-2{\\pi}s]}{s^{2}}]e^{-s^{2}t}"



Now taking inverse fourier sin trasnform , we get -


"u(x,t)=\\dfrac{18}{\\pi}\\Sigma_{s=0}^{1}[\\dfrac{\\pi(-1)^{s+1}}{s}-3\\dfrac{[{\\pi}s(-1)^{s}-2{\\pi}s]}{s^{2}}]e^{-s^{2}t}sinsx"





Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog